Evaluation of Objective Signs and Subjective Symptoms of Dry Eye Disease in Patients with Inflammatory Bowel Disease. (8th January 2019) - Barta, Zsolt; Czompa, Levente; Rentka, Aniko; Zold, Eva; Remenyik, Judit; Biro, Attila; Gesztelyi, Rudolf; Zsuga, Judit; Szodoray, Peter; Kemeny-Beke, Adam
Abstract : Aim . To evaluate tear film parameters and relationship of objective clinical signs and subjective symptoms of dry eye disease (DED) in inflammatory bowel disease (IBD) subgroups. Methods . 39 patients with Crohn's disease (CD), 26 patients with ulcerative colitis (UC), and 39 control persons with no ocular symptoms or surface disorders were included in this prospective, case-control, and cross-sectional study. The ocular surface disease index (OSDI) questionnaire was applied to evaluate dry eye symptoms, and objective tests of DED were performed on both eyes of each subject. Results . The average of OSDI scores was 30.59 (±16.68) in CD patients, 24.67 (±23.48) in UC patients, and 11.19 (±5.8) in controls. Except for tear film breakup time (tBUT) and Schirmer-I values other objective parameters were better in UC patients, than in CD patients. CD patients rather than UC patients tend to develop DED. This was associated with immunosuppressant and TNF- α inhibitor use. Conclusions . Clinicians must be aware of the spectrum of DED involvement in IBD and suggest using artificial tears in order to decrease severity of ocular complications.